Hubungan kebersihan diri dengan kecacingan pada siswa kelas 3 – 5 SDN 1 Pahandut Seberang Kota Palangka Raya Tahun 2022 - Kristiani, Friska Merilia Dwi; Maulia, Desi Rahma; Toemon, Agnes Immanuela; Widayati, Ratna; Augustina, Indria; Lestarisa, Trilianty; Jabal, Arif Rahman; Adryannoor, Muhammad Rafli (Fakultas Kedokteran Universitas Palangka Raya, 2023)
Soil Transmitted Helminths (STH) are a group of intestinal nematode parasites that cause infection in humans, particularly children with poor hygiene. Ascaris lumbricoides, one of the most common intestinal nematodes, can be spread through infective eggs consumed with contaminated food or drink, as well as through dirty hands due to contaminated soil containing infective eggs. This study aims to determine the relationship between personal hygiene and worms in grade 3-5 children at SDN 1 Pahandut Seberang, Palangka Raya City.This research was conducted using the analytical observational research method with a cross sectional approach. The sample used was 41 students from grades 3-5 of SDN 1 Pahandut Seberang. This study revealed that 23 students (56.1%) had good personal cleanliness, while 18 students (43.9%) had poor personal hygiene. Two pupils (4.9%) tested positive for helminthiasis out of a total of 39 students (95.1%). According to the Fisher's Exact test, the obtained findings were p = 0.187. There is no significant correlation between personal hygiene and worm infestation.